Discordância nos diagnósticos histopatológicos pré e pós- operatórios nas pacientes com adenocarcinoma do endométrio - Piotto, Mario Augusto Silveira Bueno [UNIFESP] (2019)
Objective: This study aims to evaluate the disagreement of pre and postoperative histopathologic diagnoses, correlating them with diagnostic methods, staging and the impact on surgical management (lymph node analysis) and survival of patients with endometrial adenocarcinomas. Materials and Methods: Sixty two patients operated for endometrial cancer at Hospital São Paulo (the hospital of the Federal University of São Paulo) were retrospectively studied, from 2002 to 2011 . The preoperative histologic diagnoses of these patients were compared with the analyzes performed on the surgical specimen (uterus). Results: A statistically significant difference (p = 0.0081) of the pre and postoperative diagnoses was shown; most of the differences occurred with worsening of the diagnosis (seven patients with low- grade disease became high-grade) and only one patient was better diagnosed after these examinations. Studying the involvement of the lymph nodes by the calculation we obtained a p= 0.00080, showing an important relation with the disease of high degree. We did not obtain a statistically significant relationship in the comparison of the pre and postoperative diagnoses with the diagnostic method and the patients survival; although it presented a statistical relation of the global survival with histological type of the tumor. Conclusion: With these results, we concluded that we should not only use the pre-operative histopathological grade to abstain from doing lymphadenectomy in patients with low- or high-grade endometrial cancer and patients who have the low- grade postoperative histopathologic diagnosis have a longer survival and free disease interval than the other patients.